Fear of Missing Out, Online Social Comparison, and Self-Identity Formation among Early Adolescents: A Qualitative Case Study in Indonesian Junior Secondary Schools - Yanny Kikis Arlint; Septina Alrianingrum; Kusnul Khotimah (Yayasan Darussalam Bengkulu, 2026)
Early adolescence is a critical period for self-identity formation, yet this developmental task is increasingly negotiated within social media environments that intensify Fear of Missing Out (FoMO), online social comparison, and external validation. This study examines how FoMO and online social comparison shape identity exploration and commitment among early adolescents in Indonesian junior secondary schools. Using a qualitative case study design, data were collected in three public schools in South Surabaya. A screening questionnaire was administered to 270 Grade VIII students, followed by purposive selection of 27 adolescents aged 12-15 years for semi-structured interviews, classroom observations, field notes, and ethically guided digital content analysis. Data were analyzed through interactive qualitative analysis supported by source triangulation, member checking, and peer debriefing. The findings show that FoMO manifested as disconnection anxiety, compulsive checking of engagement metrics, trend-based conformity, and dependence on peer validation. Online social comparison widened the discrepancy between actual and ideal selves, producing fluctuating self-esteem and self-concept incongruence. Within Marcia's identity status framework, participants predominantly displayed anxious identity moratorium and premature identity foreclosure. The study contributes to adolescent identity theory by contextualizing FoMO within a collectivist Indonesian school setting and highlights the need for critical digital literacy and school-based counseling interventions.